2021
DOI: 10.21608/ejfs.2021.44711.1081
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic and Anti-Obesity Effects of Radish Sprouts (Raphanus Sativus) in Adult Females

Abstract: R ED radish sprouts (RRS) (Raphanus sativus) are rich sources of health-promoting phytochemicals more than in its seeds.The present study aimed to evaluate the protection efficiency of red radish sprouts as hypocholesterolemic and antiobesity agents in adult females. Forty-five females with body mass index (BMI) ˃28 and aged between 25 and 40 years were randomly divided into three groups each one containing 15 females; RRS group and the controls. G1 (the first control) consumed their usual diet, while the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A sole study evaluated red radish sprouts, included in the diet of obese women as hypocholesterolemic and anti-obesity agents, but they also determined the TSH level in blood. Results revealed insignificant differences in the TSH level of all subjects before and after participating in this study [81]. Procedures: subjects with no breakfast, given a tracer dose of 100 microcuries of radioactive iodine in physiological saline; the uptake of radioactive iodine by the thyroid determined, followed by the instruction for the subjects to eat certain food such as cruciferous vegetables…”
Section: Radishmentioning
confidence: 99%
“…A sole study evaluated red radish sprouts, included in the diet of obese women as hypocholesterolemic and anti-obesity agents, but they also determined the TSH level in blood. Results revealed insignificant differences in the TSH level of all subjects before and after participating in this study [81]. Procedures: subjects with no breakfast, given a tracer dose of 100 microcuries of radioactive iodine in physiological saline; the uptake of radioactive iodine by the thyroid determined, followed by the instruction for the subjects to eat certain food such as cruciferous vegetables…”
Section: Radishmentioning
confidence: 99%
“…21 In addition to benefits for the production, RSP contains significantly higher amounts of GLSs, ITCs and phenolics than their mature root. However, although some previous studies reported the superior antioxidant activity 22 and anti-obesity effects of RSP, [23][24][25] the optimal conditions for RSP extract with high SFEN content have not yet been investigated, considering multiple variables during germination or extraction. There is still the need to explore optimal production methods of RSP extract based on bioactive compound content for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…A consequential study [26] states that flavonoids are one of the essential compounds in plants that have a protective effect on the liver, especially from toxins that accumulate in the body, indicating the importance of the radish plant. Results of a recent study show that, for the first time, the potential role in the decline of hyperlipidemia and obesity in adult females consuming radish, as it reduces the rise in body weight, blood cholesterol, blood triglycerides, and glucose [27]. Purslane, Portulaca oleraceae, is a succulent plant belongs to the family Portulacaca [28].…”
Section: Introductionmentioning
confidence: 99%